DEVELOPMENT OF BAMBOOZLE LEARNING MEDIA BASED ON A TEAM GAME TOURNAMENT TO INCREASE STUDENT LEARNING MOTIVATION - Zhafira, Dina; Syahputra, Edi; Mansyur, Abil (JME (Journal of Mathematics Education), 2025)
Encouraging student motivation requires a supportive classroomlearning atmosphere. This study addresses this challenge inmathematics education by developing learning media calledBamboozle. Bamboozle is an online-based learning platform. It wasplayed in tournament mode and employs a keypad as quizzes. Thisresearch was integrated Bamboozle into a cooperative learningmodel—Team Game Tournament (TGT)—and applied to GradeVIII MTsN 1 Medan, focusing on the topic of relations andfunctions. This study used the 4-D model. First, identified theneeds (Define), made media draft (Design), improved with experthelp (Develop), and tested in a small trial (Disseminate). Theresults indicate that the media achieved valid scores in terms ofcontent (3,95), construct (3,91), and media itself (3,92). Theincrease in students’ motivation, from 51.83 to 71.9, falls withinthe medium category based on the N-gain analysis and percentageof positive response above 95% for almost all indicators, indicatingits effectiveness. Additionally, the media was found to be practical,with students and teachers reporting ease of use and suitability withclass time. These findings suggest that Bamboozle has the potentialto enhance student motivation in learning mathematics,particularly when appropriate classroom preparation is ensured.